Retention of chlorine-36 by a cementitious backfill. (2nd January 2018) - van Es, E.; Hinchliff, J.; Felipe-Sotelo, M.; Milodowski, A.E.; Field, L.P.; Evans, N.D.M.; Read, D.
Abstract: Radial diffusion experiments have been carried out to assess the migration of 36 Cl, as chloride, through a cementitious backfill material. Further experiments in the presence of cellulose degradation products were performed to assess the effect of organic ligands on the extent and rate of chloride diffusion. Results show that breakthrough of 36 Cl is dependent on chloride concentration: as the carrier concentration increases, both breakthrough time and the quantity retained by the cement matrix decreases. Experiments in the presence of cellulose degradation products also show a decrease in time to initial breakthrough. However, uptake at various carrier concentrations in the presence of organic ligands converges at 45% of the initial concentration as equilibrium is reached. The results are consistent with organic ligands blocking sites on the cement that would otherwise be available for chloride binding, though further work is required to confirm that this is the case. Post-experimental digital autoradiographs of the cement cylinders, and elemental mapping showed evidence of increased 36 Cl activity associated with black ash-like particles in the matrix, believed to correspond to partially hydrated glassy calcium-silicate-sulfate-rich clinker.